Noninvasive Biomarkers in Assessment of Liver Fibrosis in Patients with HBeAg Negative Chronic Hepatitis B - Dimzova, Marija; Kondova Topuzovska, Irena; Bosilkovski, Mile; Ivanovski, Ljubomir; Milenkovic, Zvonko; Semenakova-Cvetkovska, Vesna; Orovcanec, Nikola (Scientific Foundation SPIROSKI, 2018)
Liver biopsy for evaluation of liver fibrosis has several adverse effects, for which reason noninvasive tests have been developed. AIM: To evaluate the usefulness of noninvasive biomarkers, qHBsAg and HBV DNA levels in predicting liver fibrosis in patients with hepatitis Be antigen (HBeAg) negative chronic hepatitis B (CHB). MATERIAL AND METHODS: This prospective study included 50 patients with HBeAg negative CHB. All patients underwent laboratory and serology testing, quantification of HBV DNA and HBs antigen. The liver stiffness was measured with elastography. The patients were analysed for APRI and FIB-4, quantitative hepatitis Bs antigen and HBV DNA. RESULTS: Logistic regression analysis showed that greatest significance in predicting liver fibrosis has FIB-4 (Wald = 3.24, P = 0.07), followed by HBV DNA ≥ 2 000 IU/ml ≤ 20 000 IU/ml (Wald = 2.86, P = 0.09), qHBsAg (Wald = 2.17, P = 0.14), HBV DNA > 20 000 IU/ml (Wald = 0.58, P = 0.45), APRI (Wald = 0.04, P = 0.84). CONCLUSION: the FIB-4 index has the greatest value in predicting liver fibrosis while APRI has the lowest; the more advanced liver disease is associated with lower serum level of quantitative HBs antigen. Combination of noninvasive blood biomarkers and imaging tests can provide better diagnostic accuracy and exclude the need for liver biopsy.